PERAN INTERNAL AUDIT DALAM PENGAMBILAN KEPUTUSAN MANAJERIAL PADA HOTEL Y SURABAYA - Dewa, Nicholas Bintang Satria; Islamudin, Ardhi (Program Studi Akuntansi Universitas Flores, 2026)
This study aims to explore the role of internal audit, particularly income audit, in supporting strategic managerial decision-making within the hotel industry. The research adopts a descriptive qualitative approach, with data collected through direct observation and in-depth interviews with two informants from the hotel's finance department. The findings reveal that internal audit significantly contributes to ensuring the accuracy of daily revenue reporting, which serves as a crucial basis for managerial decision-making. The audit reports are utilized not only for control purposes but also as tools for performance evaluation, budget planning, and operational strategy development. However, the study also identifies a weakness in the current audit process, which relies heavily on manual procedures and lacks technological integration—leading to a higher risk of human error. Therefore, continuous training and the implementation of digital audit systems are recommended to enhance the effectiveness of internal audit in supporting good governance.